Down-regulation of CD46 by Piliated Neisseria gonorrhoeae - Gill, Darcy B. (The Rockefeller University Press, 2003)

(untitled)
Human membrane cofactor protein (CD46) protects host cells against complement attack and may function as a receptor for pathogenic Neisseriae. We assessed CD46 expression in the human cervical cell line ME-180 after exposure to Neisseria gonorrhoeae. Piliated but not nonpiliated gonococci adhered to cells and produced up to an 80% reduction in CD46 surface expression by 6 h that persisted for at least 24 h. This response required a minimum multiplicity of infection of 10 and was not prevented by antibodies to CD46. CD46 down-regulation was not attributable to intracellular retention or a global or specific shutdown of mRNA or protein synthesis. Substantial quantities of CD46 were found in the supernatants, indicating a specific shedding of this protein. Adherent gonococci lacking the pilus retraction protein PilT did not down-regulate CD46 but de-repression of pilT expression restored CD46 down-regulation. After experimental infection of human volunteers with a gonococcal variant incapable of inducing CD46 down-regulation, variants of this strain were reisolated that exhibited CD46 down-regulation. Pilus-mediated interactions of gonococci with human epithelial cells results in a pathogen-induced manipulation of the host cell environment in which a membrane protein is removed from epithelial cells by liberation into the surrounding milieu.